Indígenas, catequese e civilização no município da vila de São José de Porto Alegre, Bahia (1842-1849) (Federal University of Fronteira Sul, 2023)
This article aims to describe the initiatives of the Provincial Government of Bahia to catechize and civilize the so-called “savage indians” of the municipality of São José de Porto Alegre (1842-1849). First, the presence of indigenous people in the municipality of São José de Porto Alegre is discussed, highlighting their conflicts with settlers. Then, we present the authorities' perceptions about the best means to catechize and civilize the natives, highlighting two methods: the foundation of a village and a military colony. Next, the village foundation is analyzed, showing its failure due to the lack of missionaries and, mainly, the natives’ resistance to the village. Afterward, the initiative to establish the military colony is examined, showing its failure due to the poor adaptability of the non-indigenous people to the jungle and the lack of adequate financial means. Finally, we conclude by emphasizing the government’s inability to adequately promote catechesis and civilization and the absence of public authorities in the Mucuri region.